Improvement of functional properties of gas-thermal coatings by electro-contact treatment - Smirnov, I.; Lopata, A.; Smirnova, T.; Lopata, L. (Problems of Tribology, 2020)
Among the current technological and material study areas of science and technology, the problem of surface engineering is one of the most significant. Combination of coating deposition with the following modification of the surface and its treatment is especially up-to-date. The creation of coatings ensuring the operability of machines and equipment in extreme conditions of operation has been and remains relevant. There are various techniques for deposition of protective coatings